Coal Kuznets Curve in INDIA - Beşe, Emrah; Friday, H. Swint (Journal of Applied Business and Economics, 2021)
In this study, the relationship between economic growth and emissions from coal consumption per capita is analyzed in India for the period 1960 to 2019. Although coal constitutes 70% of energy needs of India currently, India has been investing significantly in renewable energy to make clean energy meet half of its needs in the near future. This study does not confirm relationship between emissions and economic growth in the long-run in per capita terms. Total consumption terms may be analyzed in the future studies since this study does not analyze the total consumption terms because the model does not satisfy the stability requirements. For per capita analysis, the result is inverted N relationship between emissions and economic growth. Although the coefficients are insignificant, inverted N relationship between economic growth and emissions shows that there may be unsustainability in economic activities due to economic policies in India. Future studies may analyze different periods with different methodologies in India for the relationship between coal consumption and economic growth.